A new kind of nanohybrid poly(tetradecyl methyl-acrylate)-graphene oxide as pour point depressant to evaluate the cold flow properties and exhaust gas emissions of diesel fuels. (15th March 2018) - Zhao, Zhicheng; Yan, Song; Lian, Jun; Chang, Wei; Xue, Yuan; He, Zhongyi; Bi, Dongsu; Han, Sheng
Highlights: The PMA14 -GO nanohybrid PPDs exhibited better cold flow properties. Diesel fuel treated with 0.2 wt% PMA14 -6GO exhibited the best depression on CFPP, while 0.2 wt% PMA14 -9GO showed the best depression effect on SP. PMA14 -GO nanohybrid PPDs could effective improve the low-temperature viscosity of diesel fuels. PMA14 -GO nanohybrid PPDs effectively modified the crystal morphology and crystallization behavior of diesel fuels. The exhaust gas emissions of PMA14 -GO nanohybrid PPDs on diesel fuels were reported. Abstract: In this paper, a new kind of nanohybrid poly(tetradecyl methyl-acrylate)-graphene oxide (PMA14 -GO) as pour point depressant (PPD) was prepared from graphene oxide, using matrix via in situ free radical polymerization. The effect of PMA14 -GO (i.e., PMA14 -3GO, PMA14 -6GO and PMA14 -9GO) PPDs on the cold flow properties and exhaust gas emissions of diesel fuels were studied. Results indicated that PMA14 -GO PPDs exhibited a better effect on cold filter plugging point (CFPP) and solidifying point (SP) than that of PMA14 . Among them, PMA14 -6GO and PMA14 -9GO were the most suitable candidates for improving CFPP and SP. Specifically, upon addition of 0.2 wt% PMA14 -6GO could reduce the CFPP of diesel by 14 °C, and 0.2 wt% PMA14 -9GO reduced the SP of diesel by 19 °C. Moreover, PMA14 -GO PPDs could effectively lower the low-temperature. Other fuel properties were also determined and compared with the ASTM D975 . Given the heterogeneous nucleation mechanism, uniform and tiny particle-shaped crystals were observed by polarizing optical microscopy and differential scanning calorimetry. In addition, burning diesel fuel with PMA14 -GO PPDs effectively reduced HC and CO emissions, whereas NO and CO2 emissions increased with the increased engine speed at full load.